1996
DOI: 10.1207/s15327752jpa6703_16
|View full text |Cite
|
Sign up to set email alerts
|

Personal Problem-Solving Scoring of TAT Responses: Known-Groups Validation

Abstract: Two studies employed a known-groups validation strategy to evaluate a Thematic Apperception Test (TAT) scoring system purported to measure personal problem-solving skills, the Personal Problem-Solving System (PPSS). In Study 1 clinicians rated the records of 46 mental health outpatients for the presence of personal problem-solving skills deficits. Verbatim TAT transcripts from these patients were blindly scored using the PPSS. Participants predicted to demonstrate problem-solving deficits obtained lower PPSS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The Personal Problem-Solving System (PPSS; Ronan, 1990) is a performance-based measure that uses standard stimuli (i.e., Thematic Apperception Test Cards 1, 2, and 4; Murray, 1943) to evoke social problem-solving processes that are then scored using a standardized rating system (Ronan, Colavito, & Hammontree, 1993; Ronan, Date, & Weisbrod, 1995; Ronan et al, 1996). These stimuli are conceptualized as depicting social and personal problems to which the participant is asked to respond.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Personal Problem-Solving System (PPSS; Ronan, 1990) is a performance-based measure that uses standard stimuli (i.e., Thematic Apperception Test Cards 1, 2, and 4; Murray, 1943) to evoke social problem-solving processes that are then scored using a standardized rating system (Ronan, Colavito, & Hammontree, 1993; Ronan, Date, & Weisbrod, 1995; Ronan et al, 1996). These stimuli are conceptualized as depicting social and personal problems to which the participant is asked to respond.…”
Section: Methodsmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. (Ronan et al, 1996), and it is sensitive to social problem-solving training (Ronan et al, 1995). Interrater reliability estimates range from r ϭ .83 to r ϭ .92 (Ronan & Gibbs, 1997).…”
Section: Problem Solving and Community Integrationmentioning
confidence: 99%
“…A number of other potentially useful TAT scoring schemes have been developed in recent years. For example, Ronan and his colleagues (Ronan, Colavito, & Hammontree, 1993; Ronan et al, 1996) have derived an index of personal problem-solving from the TAT that correlates significantly with a performance measure involving the generation of means-end solutions to problems, and that significantly distinguishes psychiatric patients from normals. In addition, scores on this index have been found to increase significantly following training in the generation of alternative solutions (Ronan, Date, & Weisbrod, 1995).…”
Section: Thematic Apperception Testmentioning
confidence: 99%
“…Palmer found that interactive behaviors in information search can be categorized by personality factors [28]. Another study found that problem-solving behaviors could be predicted by responses to the Thematic Apperception Test [37]. In reasoning behaviors, individual differences impact rationality and reasoning as well ( [45], [46]…”
Section: Individual Differencesmentioning
confidence: 99%